Analisis Manajemen Risiko Operasional pada Jasa Ekspedisi - Nur Maulidah, Eka; Amirah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to analyze the risks faced by expedition service businesses and to evaluate their risk management practices. The research employs a descriptive quantitative approach, with data collected through a structured questionnaire covering the stages of risk identification, risk evaluation and measurement, and risk management. Data analysis was conducted using descriptive statistics by calculating the mean value of each risk indicator. The results indicate that operational risk, competition and financial risk, technology and data risk, as well as security and asset risk fall into the high-risk category, particularly delivery delays, package accumulation in warehouses, and price competition. Nevertheless, most expedition service providers have implemented fairly effective risk management practices through the use of security systems, routine fleet maintenance, compliance with regulations, and asset insurance, thereby minimizing the impact of risks on business sustainability.